Analisis Karakteristik Konsumen dalam Pembelian Produk Pertanian di Istana Tani Pusat - Rohmatul Ummah (Universitas Islam Kadiri, 2023)
In purchasing agricultural drugs, farmers or consumers have different behaviors. The purpose of this study was to determine the characteristics of consumers who buy agricultural products at the Central Farmer's Palace. The samples taken were 50 respondents. The method used is accidental sampling. Data collection was done by interview. The analysis used in this study was descriptive analysis. The results of this study are the characteristics of consumers in buying agricultural products, the majority of respondents (86%) are male, aged between 51-60 years (48%), generally have a junior high school education (40%), who have an income of between Rp. 1,500,000 – Rp. 3,000,000.